Can an App Close the Pleasure Gap?: Changes in Gendered Patterns of Sexual Pleasure, Closeness, and Emotional Labor After a Digital Intervention - Velotta, Nicholas (My University, 2025)
Persistent gender disparities in sexual satisfaction and orgasm frequency remain a hallmark of inequality in heterosexual relationships, rooted less in biology than in entrenched cultural scripts and inequitable distributions of emotional and sexual labor. This study examines whether a digitally guided intimacy intervention can begin to recalibrate these patterns. The first "scene" of a mobile intimacy app (Arya) was evaluated using a mixed-methods, pre–post design with 180 participants in relationships. Quantitative measures captured changes in sexual satisfaction, relational closeness, and outlook; qualitative open-ended responses were thematically coded with attention to constructs from Self-Expansion Theory, Social Learning Theory, and feminist scholarship on emotional labor. Findings indicate that women experienced larger gains in sexual satisfaction than men, narrowing the "pleasure gap" modestly. Increases in satisfaction were often—but not universally—paired with greater closeness, particularly among couples who began with lower baseline intimacy. Many women described relief from the cognitive burden of planning intimacy, suggesting that digital guidance might redistribute relational labor. While exploratory and not generalizable, these results highlight the potential for technology-based interventions to disrupt entrenched sexual scripts and promote more equitable intimacy at scale.
Thesis (Master's)--University of Washington, 2025
Keywords: Gender; Intimacy; Pleasure; Sex; Technology; Sexuality; Gender studies; Sociology; Sociology